2015
DOI: 10.1111/exd.12698
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐angiogenic activity of thienopyridine derivative LCB03‐0110 by targeting VEGFR‐2 and JAK/STAT3 Signalling

Abstract: Vascular endothelial growth factor receptor-2 (VEGFR-2) and Janus kinase (JAK)/signal transducer and activator of transcription 3 (STAT3) signalling are important for tumor angiogenesis and metastasis. In this study, we identified (3-(2-(3-(morpholinomethyl)phenyl)thieno[3,2-b]pyridin-7-ylamino)phenol (LCB03-0110) as a potent angiogenesis inhibitor. LCB03-0110 inhibited VEGFR-2 and JAK/STAT3 signalling in primary cultured human endothelial cells and cancer cells. An in vitro kinase assay and molecular modellin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…STAT3 is an essential mediator of VEGF transcription by directly binding to the VEGF promoter, thereby inducing angiogenesis. 28 , 29 Our study showed that mogroside V significantly inhibited the activation of STAT3 protein in PANC-1 cancer cells concomitantly with reducing VEGF protein levels in vivo . This finding suggests that the anti-angiogenic effects of mogroside V may be due to the ability of mogroside V to prevent STAT3 activation.…”
Section: Discussionmentioning
confidence: 62%
“…STAT3 is an essential mediator of VEGF transcription by directly binding to the VEGF promoter, thereby inducing angiogenesis. 28 , 29 Our study showed that mogroside V significantly inhibited the activation of STAT3 protein in PANC-1 cancer cells concomitantly with reducing VEGF protein levels in vivo . This finding suggests that the anti-angiogenic effects of mogroside V may be due to the ability of mogroside V to prevent STAT3 activation.…”
Section: Discussionmentioning
confidence: 62%
“…Clinical evidence indicates a significant correlation between active STAT3 and VEGF in gastric cancer tissues (Choi et al, 2006). Targeting STAT3/VEGF signaling has been suggested as a promising strategy for anticancer treatment (Kim et al, 2015;Po_ zarowska and Po_ zarowski, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Discovery Studio 3.5 (Accelrys) and GOLD [50] were used for molecular docking studies [26]. The crystal structure of VEGFR-2 tyrosine kinase obtained from Protein Data Bank (PDB entry: 3VID and 2OH4) (http://www.rcsb.org/pdb/), which contains a phosphorylated activation loop, was used for the docking study [51]. The structure 3VID was selected as an EriB similar small molecule ligand co-crystalized.…”
Section: Methodsmentioning
confidence: 99%